Breaking the barriers to higher economic growth : better governance and deeper reforms in the Middle East and North Africa. - Nabli, Mustapha K. (World Bank e-Library., 2007)
The world's attention to the countries of the Middle East and North Africa (MENA) region has often been dominated by headline issues: conflict, sanctions, political turmoil, and rising oil prices. Little of this international attention has considered the broad range of development challenges facing this diverse group of countries. Breaking the Barriers reflects the collected thinking of the World Bank's Office of the Chief Economist for the MENA Region on the long-term development challenges facing the region and the reform priorities and strategies for effectively meeting these challenges. It.